Interaction of Three Conormal Waves for Semilinear Wave Equations (Journal of Partial Differential Equations, 1995)
In this paper, we consider the interaction of triple of conormal waves with different singularities for semilinear wave equations. We will show that if three characteristic hyperplanes carrying different conormal singularities intersect transversally at the origin, then the solution will be conormal with respect to the three hyperplanes, and a new singularity will be produced on the surface of the light cone at later times. We can also prove here that the strength of the new singularity will be dependent only on the weakest one and strongest one in the three hyperplanes.
Keywords: Semilinear wave equation; interaction of three singularities; conormal wave; second microlocaliution